A Comparative Study to Assess the Prevalence Rate of Obesity among School Children in A Selected Private and Government School, Salem (International Journal of Nursing Care, 2020)
A comparative study was done to assess the prevalence rate of obesity among school children in a selectedgovernment and private school, Salem. A comparative research design was adopted among 200 schoolchildren (100 Boys,100Girls) in the age group of 10 to 12 years who were selected by non probabilityconvenient sampling technique. A structured interview used for collecting demographic variable andmeasured anthropometric measurements like Height, Weight & BMI calculation. Child categorized basedon BMI scoring total score was graded as According to CDC . The findings revealed that in governmentschool majority of children (48%) have normal BMI , 12% are obese, 30% are overweight and 10% areunder weight. In private school majority of children (58%) have normal BMI , 18% are obese, 4% areoverweight & 20% are under weight. Obesity was higher among children from private school (18%) thanfrom Government school (12%).
Keywords: Children, Obesity, Prevalence rate, BMI-Body Mass Index, CDC -Centers for Disease Control.